AN UPPER BOUND FOR THE COMPLEXITY OF LINEARIZED COVERINGS IN A FINITE FIELD - Nurijanyan, H. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
The minimal number of systems of linear equations with n unknowns over a finite field F_q, such that the union of all solutions of the systems forms an exact cover for a given subset in F_q^n, is the complexity of a linearized covering. An upper bound for the complexity for “almost all” subsets in F_q^n is presented.